Crossing boundaries: an excavation into an interdisciplinary approach to theatre making with specific reference to body mapping - Lambert, Roger Gordon Paul (My University, 2010)
ABSTRACT This study analyses through a Practice as Research methodology an interdisciplinary approach to theatre making. The capacity for the process of Body Mapping to form part of the theatre making process is assessed. Structured and unstructured improvisational techniques (including Body Mapping and contact improvisation) are used in facilitating four subjects who are actively involved in the creative process as performer-creators. The material generated from these sessions is then crafted into a performance work, as well as exposing the creative process in an exhibition of photographs and writings drawn from the improvisational workshops. The documentation is then consolidated in the form of a research report analysing the use of interdisciplinary approaches to theatre making with specific reference to Body Mapping.